2019
DOI: 10.1021/acs.jafc.9b06254
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Engineering of Cyanobacteria to Enhance the Production of α-Farnesene from CO2

Abstract: Photosynthetic cyanobacteria can fix CO2 and utilize it as the sole carbon source for cell growth and production of biochemicals. Here, we metabolically engineered Synechococcus elongatus PCC 7942 for an enhanced production of α-farnesene by optimizing the ribosome-binding site (RBS) of the codon-optimized farnesene synthase gene. The production of α-farnesene was found to be enhanced in strains with a low translation initiation rate, resulting in α-farnesene production (0.57 mg/(L day)). Using the RBS variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…2012, Lai and Lan 2015, Pattharaprachayakul et al. 2019, Choi and Woo 2020), and high genetic and metabolic diversity (Bolch et al. 1999, Welker et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2012, Lai and Lan 2015, Pattharaprachayakul et al. 2019, Choi and Woo 2020), and high genetic and metabolic diversity (Bolch et al. 1999, Welker et al.…”
mentioning
confidence: 99%
“…Key index words: Carbon storage; Cyanobacteria; Horizontal gene transfer; Polyhydroxyalkanoates; Polyhydroxybutyrate Abbreviations: HGT, horizontal gene transfer; LDs, neutral lipid droplets; NRPs, nonribosomal peptides; PHAs, polyhydroxyalkanoates; PHB, poly-3hydroxybutyrate Cyanobacteria are good candidates for the development and production of bioproducts due to their short life cycles, ease of genetic manipulation (Rosgaard et al 2012, Lai and Lan 2015, Pattharaprachayakul et al 2019, Choi and Woo 2020, and high genetic and metabolic diversity (Bolch et al 1999, Welker et al 2006, Beck et al 2012) resulting in part due to a rich history of horizontal transfer of genes (Matzke et al 2014, Wang et al 2020, and in some cases entire operons (Marin et al 2007, Rae et al 2011. Their ability to fix carbon dioxide (Asada et al 1999, Peramuna and Summers 2014, Velu et al 2020, and, in some cases nitrogen (Do Nascimento et al 2015, Chittapun et al 2018, Godlewska et al 2019, in addition to their tolerance for wide ranges of pH, salinity, and temperature (Hirooka et al 2014, Varshney et al 2015, give cyanobacteria potential cost-saving advantages when used for the production of bioproducts (Georgianna andMayfield 2012, Singh et al 2016).…”
mentioning
confidence: 99%
“…In Synechococcus PCC 7942 (Table 2), the most frequently employed chromosomal neutral sites are NSI (GenBank accession n • U30252), NSII (GenBank accession U44761) [253]), and NSIII (GenBank accession ABB56771.1) [254,255]. Photoproduction of isobutyraldehyde [360] Photoproduction of 1-butanol [361,362] Analysis of carboxysomes [363,364] Photoproduction of isopropanol [364] Photoproduction of isobutanol [365] Photoproduction of 3-hydroxypropionic acid [366] Photoproduction of 1,3-propanediol [367] Photoproduction of amorphadiene and squalene [368] Photoproduction of limonene [369] Photoproduction of acetone [370] Photoproduction of isoprene [371] Analysis of gene-expression control systems [372] Photoproduction of 2,3-butanediol [373] Photoproduction of farnesene [374,375] Photoproduction of lactate [376] NSI and NSIII Photoproduction of biomass and sucrose export [377] Photoproduction of a synthetic CO 2 -fixing photorespiratory bypass [378] Photoproduction of 2,3 butanediol [379] Photoproduction of amorphadiene or squalene [380] NSI, NSII, and NSIII Overproduction of transporters to facilitate sugar export [254] Promoter analysis [381] Photoproduction of polyketides [382] Analysis of the influence of pilus biogenesis on the natural transformation [229] psbA1 Photoproduction of ethylene [383] glgc Photoproduction of isobutanol [366]…”
Section: Slr0168 Psba2 and Slr2030-slr2031 Intergenic Regionmentioning
confidence: 99%
“…61 Later, Pattharaprachayakul et al reported the α-farnesene production in S. elongates PCC 7942, and the titer reached 13.0 mg/L by optimizing the expression components of FS and adaptive evolution of strains. 62 Currently, the research on farnesene production in cyanobacteria remains stuck in the laboratory stage, owing to the bottleneck associated with the low yield. The lack of highly efficient genetic editing tools and genetic components resulted in the MVA pathway not being introduced into cyanobacteria.…”
Section: Engineered Strain Of Cyanobacteriamentioning
confidence: 99%
“…81,82 Moreover, the sequential error-prone polymerase chain reaction (PCR) was selected for screening random mutants of FS with high catalytic activity. 62 In this study, more than 500 FS mutant strains were obtained by measuring the level of intracellular inorganic pyrophosphate (PPi). However, the mutant strains with FS activity exceeding that of the control group were not found, possibly because the lack of a fluoresce-based biosensor has hindered the development of a FACS-assisted AFS system.…”
Section: Farnesene Synthasethe Key Enzyme For Farnesene Biosynthesismentioning
confidence: 99%